Well Control Strategies for Effective CO2 Subsurface Storage: Optimization and Policies - Ismail Ismail; Vassilis Gaganis (Materials Proceedings)
To combat the detrimental impacts of climate change and meet the obligations outlined in the 2015 Paris Agreement, Carbon Capture, Utilization, and Storage (CCUS) has emerged as a crucial technology with significant potential for achieving climate targets. CCUS involves the capture, storage, and utilization of carbon dioxide (CO2) emissions from existing energy infrastructure, hard-to-abate industries, or directly from the atmosphere, presenting a promising solution for emission reduction. However, fully harnessing the benefits of carbon storage requires the development of technically robust, safe, and cost-effective well control strategies that align with fundamental subsurface policies. This study aims to offer a comprehensive reference guide for carbon storage applications by reviewing relevant research in the field and establishing key subsurface storage policies for carbon storage in saline aquifer formation along with their practical implementation in carbon storage development plans. Additionally, we explore the utilization of optimization techniques employed thus far in the development of effective well control strategies in saline aquifers, presenting mathematical tools utilized and the achieved results.